CEP Calculation Based on Weighted Bayesian Mixture Model - Peng, Xiaojun; Li, Chang; Duan, Xiaojun; Zhang, Shengdi; Zhang, Qiang (Mathematical problems in engineering, 2017)
CEP is an important accuracy index in the test evaluation for guidance weapon systems. As for the samples origin from diverse populations, which is a general case in the practice, traditional method with one population is inaccurate to give estimate directly. A weighted method considering the credibility of the prior information is proposed for Bayesian estimation algorithm and the weighted estimation of normal distribution parameters is provided. And the statistical diversity between the weighted and classical methods is quantified, and upper bound of the calculation errors caused by prior distortion is deduced for mixture of finite normal distributions. Taking the estimation of the dispersion of the guided weapon impact points as an example, the conclusion is drawn that our method is credible.